2014
DOI: 10.1089/sur.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Signaling in the Gut: A Novel Mechanism of Barrier Protection through Activation of Enteric Glia Cells

Abstract: A pharmacologic nicotinic cholinergic agonist increased EGC activation and improved intestinal epithelial barrier function in an in vitro model of intestinal injury. Nicotine-activated EGCs appear to modulate barrier function by preventing the activation of the NF-κB pathway. Therapies aimed at activating EGCs may have important clinical applications for improving intestinal barrier function after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…As a role for α7nAChRs in leukocyte homeostasis is unequivocal (16), CHRFAM7A might then confer leukocytes with a humanspecific responsiveness to trophic stimuli that remains to be defined. In one example, efferent signaling of the vagus nerve has a central role in regulating inflammation and α7nAChR activation is an obligatory intermediate, at least in mice (2,(16)(17)(18)(19)29,63,64). If the vagus nerve were presumed to have a similarly critical role in maintaining immune homeostasis in humans, then CHRFAM7A would likely gauge the immunomodulatory properties of human α7nAChR in a human-specific manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a role for α7nAChRs in leukocyte homeostasis is unequivocal (16), CHRFAM7A might then confer leukocytes with a humanspecific responsiveness to trophic stimuli that remains to be defined. In one example, efferent signaling of the vagus nerve has a central role in regulating inflammation and α7nAChR activation is an obligatory intermediate, at least in mice (2,(16)(17)(18)(19)29,63,64). If the vagus nerve were presumed to have a similarly critical role in maintaining immune homeostasis in humans, then CHRFAM7A would likely gauge the immunomodulatory properties of human α7nAChR in a human-specific manner.…”
Section: Resultsmentioning
confidence: 99%
“…As recently reviewed by Costantini et al (2) and Sinkus et al (3), it was almost twenty years later that Gault et al (4) sequenced the human α7nAChR gene on chromosome 15q13-14 and found it to be structurally similar to that of all other species. At the same time, however, they noted the presence of a second, human-specific partially duplicated α7nAChR-like gene that localized 1.6 Mb 5′ upstream from human CHRNA7 (4).…”
Section: Introductionmentioning
confidence: 98%
“…The concentrations of nicotine used in our cell culture studies were derived from detailed dose-response testing, were noncytotoxic, and induced significant effects at levels higher than those absorbed in the circulation by individuals who smoke, but which may be achieved in tissue levels with high nicotine concentrations, such as the lung (6,30). The effect of nicotine on barrier function may be organ dependent because other studies have shown an improvement in the gut barrier function by cholinergic actions of nicotine on enteric glial cells (4).…”
Section: Discussionmentioning
confidence: 99%
“…mechanism for this effect (58)(59)(60). Enteric glia express TLRs, and these are differentially upregulated in response to pathogenic and non-pathogenic bacteria (61,62).…”
Section: Role Of Enteric Glia In Brain Disordersmentioning
confidence: 99%